Polyphenolic Profile and Antioxidant Activity of Leaf Purified Hydroalcoholic Extracts from Seven Mexican Persea americana Cultivars - Castro López, Cecilia; Bautista Hernández, Israel; González Hernández, María D.; Martínez Ávila, Guillermo Cristian Guadalupe; Rojas, Romeo; Gutiérrez Díez, Adriana; Medina Herrera, Nancy; Aguirre Arzola, Víctor Eustorgio (2019)
Persea americana (avocado) is a fruit consumed worldwide; however, since avocado leaves are apparently a natural ingredient that can be used as a traditional medicine, they can be a potential source of bioactive compounds. This study aimed to analyze the antioxidant activity of seven Mexican avocado leaf extracts by DPPH•, ABTS•+, and lipid peroxidation (LPO), and to identify the compoundproﬁlebyliquidchromatographycoupledtomassspectrometry/electronsprayionization. The highest free radical-scavenging activity was observed for Platano Delgado and Criollo 6 avocado cultivars havin IC50 values of 271.86 ± 13.69 and 269.56 ± 6.53 for DPPH• and ABTS•+ radicals, respectively, while the best result for lipid oxidation inhibition was registered in Criollo 6 cultivar extract. Inthisstudyfortyonecompoundsweredetectedinavocadoleavesofthethesevencultivars analyzed, and of these compounds, eighteen phenolics were identiﬁed for ﬁrst time in such plant material. The present study demonstrated that Mexican cultivars of Persea americana possess diverse polyphenolic compounds with strong antioxidant activity, which might be useful in the food and pharmaceutical industries.